Referentes teóricos para la autoevaluación del proyecto curricular de ingeniería de Sistemas de la Universidad Distrital - Perez Castillo, José Nelson; Castro Vargas, Blanca Magdalena (Ingeniería, 1999)
Acreditation recomended by the CNA is not a compulsory process, except for those faculties which main area of knowledge is education. Nevertheless, to be updated with the postmodernity criteria, it is necessary to get a social recognition by comparing the programme with academic pairs in a national and international field. Self evaluation as the first step of the acreditation process must be faced from an epistemological point of view to get the expected goals.